The Impact of Capital on Profitability and Risk-Taking: Evidence from the US Banks - SAHA, PRAPTI (My University, 2025)
This thesis explores the connection between bank capital, profitability, and risk-taking within the banking industry in the United States and especially focuses on the difference in these effects between banks of different sizes. The research examines five types of FDIC size (very small, small, medium, large, and very large/G-SIBs) using a panel dataset from 2000 to 2023, and consequently, studies the heterogeneity in business model, regulatory exposure, economic resilience, and strategic capital use. The research time frame covers several crises and post-crisis periods, such as the Global Financial Crisis (2007-2009), the COVID-19 pandemic (2020-2021), and the recent interest rate shock (2022-2023), which allows for evaluating the capital behavior during normal and stressful periods. The paper has used fixed effects and System GMM estimators to overcome unobserved heterogeneity and possible endogeneity of capital and performance. ROA, ROE, and NIM are used to measure profitability, and Z-score, non-performing loans, and net charge-offs measure risk-taking. The results demonstrate that increased capital can enhance profitability, especially in terms of ROA and net interest margins, which suggest that well-capitalized banks incur less funding costs and have better performance that is driven by stability. The implications on ROE, however, are less significant in very large banks, which indicates leverage dilution and the trade-off between stability and shareholder returns. The findings also indicate that there is a strong positive relationship between capital and financial stability (Z-score) of all sizes, but the decrease in credit risk (NPLs and charge-offs) is greatest at very small and small banks. The research concludes by stating that the capital-profitability-risk nexus is context and size-dependent. Small and community banks deploy capital as a signal of solvency and confidence, but large and very large banks deploy capital as a buffering system to diversify their strategies and off-balance-sheet growth. The results have significant regulatory implications, especially in proportional capital requirements design. A single-fit regulation has the risk of overloading smaller institutions whilst failing to capture the complexity of risk in G-SIBs. This thesis makes a contribution to current arguments on resilience, prudential policy, and the changing nature of the structure of U.S. banking by combining size segmentation with recent regulatory cycles.

Tämän pro gradu -tutkielman tarkoituksena on tarkastella pankkien pääoman, kannattavuuden ja riskinoton välistä yhteyttä Yhdysvaltojen pankkisektorilla sekä analysoida, kuinka nämä vaikutukset eroavat pankkien kokoluokittain. Tutkimus hyödyntää FDIC:n kokoluokitusta (erittäin pienet, pienet, keskisuuret, suuret ja erittäin suuret/G-SIB-pankit) ja paneeliaineistoa vuosilta 2000–2023. Aineisto mahdollistaa erilaisten liiketoimintamallien, sääntelyrasitusten, taloudellisen kestävyyden sekä pääoman strategisen käytön kokoluokittaisen tarkastelun. Tutkimusajanjakso kattaa useita kriisi- ja jälkikriisivaiheita, kuten globaalin finanssikriisin (2007–2009), COVID-19-pandemian (2020–2021) sekä viimeaikaisen korkoshokin (2022–2023), mikä mahdollistaa pääomakäyttäytymisen arvioinnin sekä normaaleina että stressijaksoina. Tutkielmassa käytetään kiinteiden vaikutusten malleja sekä System GMM -menetelmää poistamaan havaitsematonta heterogeenisuutta ja pääoman sekä suorituskykymuuttujien mahdollisia endogeenisuusongelmia. Kannattavuutta mitataan ROA-, ROE- ja NIM-muuttujilla, ja riskinottoa Z-score-arvolla, järjestämättömillä luotoilla sekä luottotappioilla. Tulokset osoittavat, että vahvempi pääomitus lisää kannattavuutta erityisesti ROA:n ja nettorahoitusmarginaalin kautta, mikä viittaa pienempiin varainhankintakustannuksiin ja vakauden kautta syntyvään parempaan tuloksentekokykyyn. ROE-vaikutukset ovat kuitenkin heikompia erittäin suurissa pankeissa, mikä heijastaa velkavivun laimenemista ja vakavaraisuuden ja omistaja-arvon välistä ristiriitaa. Tulokset osoittavat myös vahvan positiivisen yhteyden pääoman ja taloudellisen vakauden (Z-score) välillä kaikissa kokoluokissa, mutta luottoriskin väheneminen (NPL:t ja luottotappiot) on suurinta erittäin pienissä ja pienissä pankeissa. Tutkimuksen johtopäätöksenä todetaan, että pääoma–kannattavuus–riskisuhde on sekä konteksti- että kokoriippuvainen. Pienet ja community-pankit käyttävät pääomaa maksukyvyn ja luotettavuuden signaalina, kun taas suuret ja erittäin suuret pankit hyödyntävät pääomia puskurijärjestelmänä ja hajauttamisstrategioiden mahdollistajana sekä taseen ulkopuolisen toiminnan kasvattajana. Tuloksilla on merkittäviä sääntelyllisiä vaikutuksia erityisesti suhteutettujen pääomavaatimusten suunnittelussa. Yhdenmukainen sääntelykehikko voi kuormittaa suhteettomasti pieniä pankkeja, mutta jäädä riittämättömäksi G-SIB-pankkien monimutkaisen riskiprofiilin kannalta. Tutkielma tarjoaa uutta tietoa Yhdysvaltain pankkisektorin vakaudesta, sääntelystä ja rakenteellisesta muutoksesta yhdistämällä kokoluokittaisen analyysin ajankohtaisiin sääntelykehityksiin.
Keywords: financial supervision; profitability; risk-taking; banking sector; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance